Starbursts versus active galactic nuclei: Studying astrochemistry of dusty galaxies. Issue 1 (31st January 2021) - Martins‐Franco, Yanna; Menéndez‐Delmestre, Karín
Abstract: Infrared luminous galaxies are rare locally but dominate the star formation activity at z ≥ 1. The study of these objects is difficult at optical wavelengths especially on account of the abundant dust. At the smallest scales, dust becomes micron‐sized molecules known as PAHs that are excited by UV photons and whose emission can be used to reveal physical properties of obscured regions that otherwise remain invisible to our instruments. We can thus use infrared spectroscopy to classify the emission in these systems as arising from star formation activity or active galactic nuclei (AGN). In this work, we go further than this and undertake an astrochemical analysis of the ISM by probing the PAH population. Based on Spitzer/IRS mid‐infrared spectra of ∼700 dusty galaxies from the GOALS and ATLAS surveys, we analyze the PAH population in terms of size, charge, and composition using the NASA Ames PAH Database, a large theoretical spectroscopic library of PAH molecules. We find that the PAH population in these galaxies is dominated by small and neutral molecules, with very little diversity in composition, beyond Carbon and Hydrogen. These results are consistent with theoretical models of PAH emission for star‐forming galaxies. We also see a weak trend of an increased proportion of charged PAHs in galaxies with a more pronounced AGN contribution, suggesting that the radiation field of the power source may ultimately affect the ISM astrochemistry. Although our results point to AGN being capable of altering PAHs molecules, PAH features are still significant in AGN regions, suggesting that the AGN does not destroy them. This is in agreement with recent laboratory works pointing and motivating further use of PAH molecules to probe for the radiation field in these dusty, extreme environments.